The Influence of the Implementation of Tri Core Breastfeeding on the Willingness of Mothers to Breastfeed at Posyandu Melati, Mekarwangi Village, West Cikarang, Bekasi Regency - Santi Rimayanti; Resi Galaupa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Mother's Milk (ASI) is the first food experienced for babies. The factors of mothers not giving exclusive breastfeeding include knowledge factors, maternal nutritional factors during pregnancy and breastfeeding, psychological, physiological and hormonal. Other factors include delayed initiation, inexperienced mothers, no family support, lack of knowledge, attitudes, behavior, socio-cultural factors, maternal nutritional status, and hospital policies that do not support lactation. Efforts are made to achieve exclusive breastfeeding such as education about breastfeeding, support, and mother's confidence. This is contained in the model, namely the Tri Core Breastfeeding ModelsPurpose: This study aims to determine whether there is an effect of the application of Tri Core Breastfeeding on the Willingness of Mothers to Breastfeed at Posyandu Melati, Mekarwangi Village, West Cikarang, Bekasi RegencyMethods: This research uses quantitative analytic research with a cross sectional study approach. Data collection used the Infant Feeding Intention Scale questionnaire while the Tri Core Breastfeeding method was carried out using booklets. The sampling technique used was accidental sampling with a total sample of 30 respondents who met the research criteria.Results: The study showed that out of 30 respondents, there were 19 (63.3%) respondents who implemented tri core breastfeeding according to the SOP and there were 11 (36.7%) respondents who implemented tri core breastfeeding did not comply with the SOP. there were 20 (66.7%) mothers willing to breastfeed well and there were 10 (33.3%) mothers willing to breastfeed less. The results of the Chi-Square statistical test obtained the value of Ï = 0.002 <Î± value of 0.05, meaning that there is an effect of the application of Tri Core Breastfeeding on the Willingness of Mothers to Breastfeed at Posyandu Melati, Mekarwangi Village, West Cikarang, Bekasi RegencySuggestion: To the midwives and health workers at Posyandu Melati, Mekarwangi Village, West Cikarang, Bekasi Regency, to be able to apply the Tricore Breastfeeding Models as additional care for mothers since pregnancy which involves the family for the success of exclusive breastfeeding